Fleas of small mammals on Reunion Island: diversity, distribution and epidemiological consequences. - Vanina Guernier; Erwan Lagadec; Gildas LeMinter; Séverine Licciardi; Elsa Balleydier; Frédéric Pagès; Anne Laudisoit; Koussay Dellagi; Pablo Tortosa (Public Library of Science (PLoS), 2014)
The diversity and geographical distribution of fleas parasitizing small mammals have been poorly investigated on Indian Ocean islands with the exception of Madagascar where endemic plague has stimulated extensive research on these arthropod vectors. In the context of an emerging flea-borne murine typhus outbreak that occurred recently in Reunion Island, we explored fleas' diversity, distribution and host specificity on Reunion Island. Small mammal hosts belonging to five introduced species were trapped from November 2012 to November 2013 along two altitudinal transects, one on the windward eastern and one on the leeward western sides of the island. A total of 960 animals were trapped, and 286 fleas were morphologically and molecularly identified. Four species were reported: (i) two cosmopolitan Xenopsylla species which appeared by far as the prominent species, X. cheopis and X. brasiliensis; (ii) fewer fleas belonging to Echidnophaga gallinacea and Leptopsylla segnis. Rattus rattus was found to be the most abundant host species in our sample, and also the most parasitized host, predominantly by X. cheopis. A marked decrease in flea abundance was observed during the cool-dry season, which indicates seasonal fluctuation in infestation. Importantly, our data reveal that flea abundance was strongly biased on the island, with 81% of all collected fleas coming from the western dry side and no Xenopsylla flea collected on almost four hundred rodents trapped along the windward humid eastern side. The possible consequences of this sharp spatio-temporal pattern are discussed in terms of flea-borne disease risks in Reunion Island, particularly with regard to plague and the currently emerging murine typhus outbreak.